2013
DOI: 10.1177/1059840513487217
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Feasibility of a Communication Intervention for Mexican Immigrant Mothers and Children in a School Setting

Abstract: Children of Mexican immigrants are exposed to multiple ecological risks that heighten their likelihood of experiencing depressive symptoms. In previous studies, affirming parent–child communication has been found to be protective against depressive symptoms in Hispanic youth. Interventions focused on enhancing communication between parents and youth have the possibility of strengthening protective factors for children. The aims of this study were to (1) adapt an evidence-based parent–child communication interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Retention of participants at each stage of the study can be found in the CONSORT table (Figure 1). Detailed description of implementation feasibility can be found in a separate publication (McNaughton et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Retention of participants at each stage of the study can be found in the CONSORT table (Figure 1). Detailed description of implementation feasibility can be found in a separate publication (McNaughton et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…The intervention is a manual-guided, mental health promotion, communication skill-building program appropriate for use in schools and designed to be delivered by school nurses, social workers, or teachers. The Family Communication intervention consists of 12 hr (6 group meetings, 2 hr each) of small group skill-building sessions with mother–child dyads and is adapted from Riesch et al’s (1993) Mission Possible: Parents and Kids who Listen program (McNaughton et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For optimal cultural adaptation, attention to the surface and deep structure must be taken into account (Escobar-Chaves et al, 2011;McNaughton, Cowell & Fogg, 2014). The surface structure would involve designing messages with observable and "superficial" characteristics of a target population (e.g., people, clothes, places, language and youthful jargon, etc.).…”
Section: Cultural Adaptation Of a Health Communication Programmesmentioning
confidence: 99%